Evaluasi Program Layanan Percepatan Profesor dan Lektor Kepala Secara Holistik Integratif di Universitas Pendidikan Ganesha - Sumiani, Ni Kadek; Sunu, I Gusti Ketut Arya; Purnamawati, I Gusti Ayu (Pascasarjana Universitas Pendidikan Ganesha, 2023)
This study aims: 1) To determine the effectiveness of the holistically integrative accelerated service program for professors and associate professors at Ganesha University of Education from the context component, 2) To determine the effectiveness of the holistically integrative accelerated service program for professors and associate professors at Ganesha University of Education from the components input, 3) To determine the effectiveness of the holistically integrative accelerated service program for professors and associate professors at Ganesha University of Education from the process component, 4) To determine the effectiveness of the holistically integrative accelerated service program for professors and associate professors at Ganesha University of Education from the product component, 5) To find out the effectiveness of the holistically integrative accelerated service program for professors and associate professors at Ganesha University of Education from the components of context, input, process, product. The research was conducted at the Ganesha Singaraja University of Education. The sampling technique used in this study used a purposive sampling technique. The data collection method is by distributing questionnaires to professors and associate professors. The steps of data analysis are as follows; 1) Change the raw score into a Z score (z-score), 2) Change the score of each CIPP variable into a T-Score, 3) Determine the direction of the T-Score of the Context, Input, Process and Product variables, 4) Determine the direction of the T- score into the Glickman quadrant. The results obtained as a whole for the holistically integrative accelerated service program for professors and associate professors at the Ganesha University of Education in terms of context, input, process, and the product obtained very effective results (+ + + +). This program needs to be maintained and continued because it has been proven to be able to improve university quality through increasing the number of professors and associate professors at Ganesha University of Education.